Neurological manifestations and PET studies of the thalamic vascular lesions - Matsuda, Shinji; Hirayama, Keizo; Kawamura, Mitsuru (Japanese Journal of Stroke, 1995)
We divided 38 patients with cerebrovascular disease of the thalamus into 5 groups according to the site of the thalamic lesions as confirmed by X-ray CT and/or MRI. In 16 patients, we examined the cerebral blood flow (CBF) and cerebral metabolic rate of oxygen (CMRO2) by positron emission tomography (PET). In the anteromedial thalamic lesion group, patients dysplayed disturbances of spontaneity, memory, reading and writing. CBF and CMRO2 were decreased in the frontal, parietal and temporal lobes on the side of the lesion. In the dorsolateral thalamic lesion group, ataxic hemiparesis was a characteristic symptom. CBF and CMRO2 were decreased in frontoparietal lobes on the side of the lesion. In the group with lesions confined to the nucleus ventralis posterioris thalami, the main symptoms were sensory disturbance, with cheiro-oral sensory syndrome being particularly evident. CBF and CMRO2 were decreased in the parietal lobe on the side of the lesion. In the group with posterolateral thalamic lesions without pulvinar involvement, patients exhibited thalamic syndrome without thalamic pain. CBF and CMRO2 were decreased in the frontoparietal and temporal lobes on the side of the lesion. In contrast, in the group with posterolateral thalamic lesions with pulvinar involvement, all patients showed thalamic pain. The decrease in CBF and CMRO2 extended to the inferomedial region of the temporal lobe in addition to the area of decreased CBF and CMRO2 observed in the group with posterolateral thalamic lesions without pulvinar involvement. Based on these results, we speculate that the neurological manifestations of thalamic vascular disease are associated with a decrease in cortical CBF and CMRO2 secondary to the thalamic ledsions.